A histochemical study on Andrograhis paniculata. - Espanola, Rennor Andrew Causing (1992.)
A histochemical study was performed on Andrographis paniculata, an herbaceous dicot of the Family Acanthaceae, to screen the plant for some medically important substances that could be present in it., Results of tests revealed alkaloids in the xylem vascular cabium, and phloem of both the leaf and stem; amygdalin in phloem of stem and root; arbutin in the calyx, ovary, and xylem of leaf, stem, and root, saponins in the seed, and xylem of leaf, stem and root; Tannins in the epidermis of stem which does not yet have periderm; formic acid in the epidermis and cortex of leaf stem, in the xylem of stem and root, and in the periderm of old stems and root. A very slight presence of oxalic acid in the pith of internode of the stem without periderm was also noted.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Andrographis paniculata